The influence of Buddhism on some aspects of Thai education - Wejaparn, Prayoon 1934- ([Quezon City s.n.], 1967)
The object of the study is to determine the influence of Buddhism on the philosophy and aims of Thai education, its curriculum, and its methods and educational practices.
Thesis (M.Ed.)--University of the Philippines
Keywords: Buddha and Buddhism -- Influence; Church and education in Thailand